2014
DOI: 10.1007/s00203-014-1074-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of starvation on survival and virulence expression of Aeromonas hydrophila from different sources

Abstract: Aeromonas hydrophila is an aquatic bacterium responsible for several human illnesses. The aim of this work was to investigate the survival ability and virulence expression of two strains from different sources (fish, strain 87 and surface water, strain LS) maintained in a seawater microcosm. The strains were analyzed for the total and viable bacterial counts, adhesion ability to Hep-2 cells and aerA gene expression by qPCR throughout the experiment (35 days). Both strains reached a putative VBNC state and lost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 36 publications
1
19
0
1
Order By: Relevance
“…The authors concluded that flow cytometry was a most appropriate technique to study VBNC aeromonads. veronii, (6%) the rest <6%; d Winter peak at water temperature <14; e Summer peak but not dependent of temperature; f Nonculturable Aeromonas population ranging from 3.4 x 10 1 to 2.4 x 10 4 cells.mL-1 was detected in the drinking water; NR: Not Reported A recent study by Casabianca et al (2015) demonstrated that in response to a stress condition two different strains of Aeromonas, one from fish and the other from seawater reduced their culturability and virulence expression but with a different behavior. The strain from fish was not detected at day 35, while the one recovered from seawater remained culturable.…”
Section: Detection Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…The authors concluded that flow cytometry was a most appropriate technique to study VBNC aeromonads. veronii, (6%) the rest <6%; d Winter peak at water temperature <14; e Summer peak but not dependent of temperature; f Nonculturable Aeromonas population ranging from 3.4 x 10 1 to 2.4 x 10 4 cells.mL-1 was detected in the drinking water; NR: Not Reported A recent study by Casabianca et al (2015) demonstrated that in response to a stress condition two different strains of Aeromonas, one from fish and the other from seawater reduced their culturability and virulence expression but with a different behavior. The strain from fish was not detected at day 35, while the one recovered from seawater remained culturable.…”
Section: Detection Methodsmentioning
confidence: 95%
“…), extracellular enzymes (hemolysins, lipases, etc. ), secretion systems and associated toxins (Type I to Type VI secretion systems), iron acquisition systems and quorum sensing (QS) communication that is further explored in many studies cited in this chapter Khajanchi et al, 2010;Pablos et al, 2010;Berg et al, 2011;Parker and Shaw, 2011;Senderovich et al, 2012;Beaz-Hidalgo and Figueras, 2013;Morinaga et al, 2013;Casabianca et al, 2015;Rasmussen-Ivey et al, 2016a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenic mechanisms associated with Aeromonas virulence is multifaceted and involves adhesins, S/A layer, lipopolysaccharides, motility, siderophores, biofilm production and an array of biologically active extracellular products and exoenzymes, that is cytotoxins, enterotoxins, aerolysin⁄haemolysins, lipases and proteases (Casabianca et al . ). While aeromonad pathogenicity is multifactorial, adhesion and colonization of diverse host cells is the most important factor for initiation of the disease process.…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, novel antimicrobial strategies need to be developed for the treatment of Aeromonas infections. Although there are a number of A. hydrophila strains with different genomic structures, the complexity of virulence factors carried by different strains has contributed to the pathogenicity of A. hydrophila (Chauret et al ; Casabianca et al ). In the past 20 yr, several virulence factors of A. hydrophila have been reported and characterized, and most of those reported contribute to A. hydrophila infections (Grim et al ).…”
mentioning
confidence: 99%